Nursing Student Satisfaction with a Crisis Management Game-Based Training; a quasi-experimental study - Mohsen Masoumian hosseini; Toktam Masoumian hosseini; karim Qayumi (طب اورژانس ایران, 2023)
Background: This study was conducted to investigate nursing student satisfaction and anxiety with an emergency and crisis management game-based training (GBT) course.